2013
DOI: 10.3109/14767058.2013.825600
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia in extreme immature preterm infants: increased risk for intracranial haemorrhage?

Abstract: Haemophiliacs and extremely premature infants are both at an increased risk for intracranial haemorrhage; both conditions might be further elevating the risk. We report a case of a very immature preterm-infant of 26 gestational weeks (birth weight 635 g) with severe haemophilia A. Furthermore, we provide an overview of the published literature on this subject matter. Until now, deficiency of factor VIII or IX as a potential risk factor for ICH in preterm infants remains controversial. However, prophylactic sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…At our centre, there were no children with mild or moderate haemophilia who experienced ICH, concurring with most other series of ICH in children with haemophilia [14]. One French study found that 50% of ICH occurred in moderate or mild haemophiliacs aged 2-15 years of age [13]; these findings are not supported in this study or other case series to date. The rarity of ICH in mild/moderate haemophilia may support the principle of early prophylaxis in young boys with severe haemophilia.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…At our centre, there were no children with mild or moderate haemophilia who experienced ICH, concurring with most other series of ICH in children with haemophilia [14]. One French study found that 50% of ICH occurred in moderate or mild haemophiliacs aged 2-15 years of age [13]; these findings are not supported in this study or other case series to date. The rarity of ICH in mild/moderate haemophilia may support the principle of early prophylaxis in young boys with severe haemophilia.…”
Section: Discussionsupporting
confidence: 85%
“…However the true prevalence of ICH is likely to be underestimated, as asymptomatic babies with ICH may not be investigated or reported . Risk factors for ICH in infants with haemophilia may include: unknown carrier status, prematurity, traumatic birth history and negative family history (FH) . Published figures of mortality resulting from ICH in haemophilia have been as high as 20%, with more recent estimates of 2.5% .…”
Section: Introductionmentioning
confidence: 99%
“…Premature children display symptoms earlier -usually in the first days after birth [16][17][18][19][20][21][22][23]. This is connected with the significant number of invasive procedures they undergo at NICU.…”
Section: Discussionmentioning
confidence: 99%
“…In other situations, however, the “factor first” principle applies, and prophylactic therapy should be strongly considered after a difficult delivery, or if significant facial or cranial bruising is present (Figure 3). Many of the premature newborns with hemophilia reported in the literature have been given prophylactic or empiric factor replacement, 52 57 and so prematurity should also prompt consideration of prophylactic factor administration (Figure 3). Plans for prophylactic and empiric therapy should be discussed before birth, and included in the written delivery plan.…”
Section: Postnatal Carementioning
confidence: 99%
“…Experience with management of premature newborns with hemophilia is limited to case reports. 52 57 Management of premature newborns should be determined on an individual basis. Delivery and postnatal care should occur at an HTC.…”
Section: Other Issuesmentioning
confidence: 99%